Inhibition of γ-glutamyl transferase suppresses airway hyperresponsiveness and airway inflammation in a mouse model of steroid resistant asthma exacerbation - Zhang, Cancan; Xu, Huisha; Netto, Keilah G.; Sokulsky, Leon A.; Miao, Yiyan; Mo, Zhongyuan; Meng, Yan; Du, Yingying; Wu, Chengyong; Han, Liyou; Zhang, Lirong; Liu, Chi; et al. (Frontiers in Immunology, 2023)
Despite recent advance, there are limited treatments available for acute asthma exacerbations. Here, we demonstrate that GGsTop, a γ-glutamyl transferase inhibitor, attenuates hallmark features of the disease with a murine model of lipopolysaccharide (LPS) and ovalbumin (OVA) driven asthma exacerbation. Expression of inflammatory cytokines, mucus hypersecretion, collagen deposition, and airway hyperresponsiveness (AHR) were dramatically inhibited by GGsTop treatment. Using RNA-sequencing and pathway analysis, we demonstrated that the activation of TLR4/NFκB signaling pathway in airway was downregulated by GGsTop. Interestingly, further analysis revealed that GGsTop significantly inhibited not only IFNγ responses but also the expression of glucocorticoid-associated molecules, implicating that GGsTop profoundly attenuates inflammatory pathways. Overall, our study suggests that GGsTop is a viable treatment for asthma exacerbation by broadly inhibiting the activation of multiple inflammatory pathways.